Прецедентні феномени як вияв мовної гри в сучасних українських Інтернет-ЗМІ - Сахарук, Інна (Видавництво Львівської політехніки, 2014)
The nature of the language game phenomenon was described, the role of precedent phenomena as a means of its implementing in the discourse of modern Ukrainian online media was analyzed. The types of precedent units transformation were distinguished.
Keywords: Інтернет-медіа; інтертекстуальність; мовна гра; постмодернізм; прецедентний феномен